Synthesis and Characterization of Novel Ligand Type N2O2 and it,s Complexes With Cu(Ð¿) Co(Ð¿), Ni(Ð¿), Zn(Ð¿), and Cd(Ð¿) ions - habet, A. T; Al-jeboori, M. J.; Abdulkarim, E. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The reaction of ethylenediamine with [2,4,6-trihydroxyacetophenon] and KOH (Schiff Base) to gives the new tetradentate ligand 2-(1-2-1-2,6-Dihydroxy-4-methyl phenyl)ethyliden amino- ethylimino-ethyl-benzene- 1,2,5-triol [HCl]. This ligand was reacted with some metal ions (Cu(II), Co(II), Ni(II), Zn(II), and Cd(II)) in methanol with (1:1) metal : ligand ratio to give a series of new complexes of the general formula [M(H4L)], where: M= Cu(11), Co(II), Ni(II), Zn(II), and Cd(II). All compounds were characterized by spectroscopic methods [I.R, U.V.-Vis, C.H.N., analysis H.P.L.C, atomic absorption, magnetic susceptibility, (EI-mass for the ligand)], and microanalysis along with conductivity measurements. From the obtained data the proposed molecular structure was suggested for [Co(H4L)], [Ni(H4L)], [Cu(H4L)], which are complexes adopting square planar structure, and [Zn(H4L) and [Cd(H4L)] which are complexes adopting a tetrahedral structure about the metal ions respectively.